Subjective sleep complaints were associated with painful temporomandibular disorders in adolescents: The Epidor-Adolescere study - Fernandes, Giovana [UNESP]; van Selms, Maurits K. A.; Lobbezoo, Frank; Aarab, Ghizlane; Braido, Guilherme Vinícius Vale do [UNESP]; Campi, Leticia Bueno [UNESP]; Jordani, Paula Cristina [UNESP]; Gonçalves, Daniela Aparecida Godoi de [UNESP] (Wiley, 2022)
Background: Sleep disturbances in adolescents has received a lot of attention in the literature and it is recognised as a serious health concern. The association between pain and sleep disturbances in adolescents has been extensively studied. However, to the best of our knowledge, there is a lack of studies investigating the association between various subjective sleep variables and painful TMD in adolescents. Objectives: to investigate the association between painful TMD and subjective sleep variables in adolescents' non-clinical sample. We conducted a cross-sectional study. TMD was classified according to the RDC/TMD criteria. The Revised Face Scale evaluated TMD pain intensity, and pressure pain thresholds (PPTs) were assessed in trigeminal and extra-trigeminal areas. The subjective sleep variables were assessed according to the Sleep Disturbance Scale for Children and Sleep Behaviour Questionnaire. Results: The final sample consisted of 690 adolescents (12.7 ± 0.76 years), with 16.2% of them presenting painful TMD. Adolescents who frequently reported waking up more than twice per night and feeling tired when awake were more likely to present painful TMD symptoms [OR = 1.7 (95% CI: 1.04–2.90); p =.034 and OR = 1.6 (95% CI: 1.01–2.48); p =.046, respectively]. The intensity of TMD pain was negatively associated with sleep quality (p =.015). Also, PPT values in the trigeminal and extra-trigeminal areas were negatively associated with total sleep time (p =.048 and p =.042, respectively). Conclusions: The present results point out the importance of considering sleep complaints associated with painful TMD in adolescents.
Keywords: adolescent; association; facial pain; sleep quality; sleep–wake disorder initiation; temporomandibular disorders